From colossal magnetoresistance to solar cells: An overview on 66 years of research into perovskites. Issue 9 (1st August 2017) - Wagner, Patrick; Wackers, Gideon; Cardinaletti, Ilaria; Manca, Jean; Vanacken, Johan
Abstract : Perovskites are a huge family of compounds to which the natural titanium mineral CaTiO3 is the common ancestor. The cubic structure looks apparently simple, but the variety of metal ions and mixtures thereof that fit into a perovskite lattice is tremendous. Even in the case that the ionic radii do not allow for a perfect cubic ordering, there are various superstructures and orbital‐ordering effects to cope elegantly with distortions. The compositional and structural flexibility offers a large toolbox to design and synthesize perovskites with tailored properties searched for by physicists, chemists, materials scientists and device engineers. These materials are equally of interest for fundamental studies and for applied research while both viewpoints cross‐fertilize each other regularly. Our overview starts with the discovery of ferromagnetism in manganites in 1950 and ranges until 2016: Today, halide perovskites are fully in focus for their potential in photovoltaic applications. This is certainly not an endpoint, but another milestone in a long series of often‐unexpected discoveries on an 'evergreen material'. Ball‐and‐stick model of the ideal cubic perovskite structure. The cation at the central position or 'B site' (small black dot) defines the group name (e.g., titanates) and plays a key role for the physical properties of the material.